วิจารณ์หนังสือ : Book Review - Gambhirasettho, Phramaha Phongsiri (Journal of Graduate MCU KhonKaen Campus, 2022)
The review of this book has the objective of studying the book "Study: Working Together, What Life Gets," which discusses human life. Education must be always available if a good life is to be lived. To live a decent and noble life, it must be a life of study, learning, training, and development, and putting in a lot of effort to be able to use it as a tool for training and self-improvement. This is to help them reach their full potential. How should they function? What kind of work do you anticipate yielding results? How to do it the work will go well, as well as teaching them to be considerate of others and to create a habit of enjoying work to sustain themselves. The work's goal is for them, or according to the work's goal, to provide good results. It's all about cyclical relationships when it comes to motivation. Work, Dhamma, and work are three vital things that will contribute to greater life harmony. People who operate in this manner will have great work and Dhamma lives. "This life is for work, and this work is for Dhamma," it says. Keywords: Study; Work Together; What Life Gets